KAJIAN KEBERLANJUTAN PENGEMBANGAN ECOVILLAGE DI DAS CITARUM HULU - Nita Nilawati Walla; Cecep Kusmana; Hikmat Ramdan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
Environmental problems occurred in the upper basin of Citarum River caused by domestic, agriculture, livestock and industrial waste were encouraged the establishment of a large-scale movement called Gerakan Citarum Bersih, Sehat, Lestari dan Indah (BESTARI) since 2014. As one approaches to the movement, ecovillage’s sustainability in 54 villages upon upper basin of Citarum River should be evaluated. Multi-Dimensional Scaling (MDS) method through Rapid Appraisal for Ecovillage (RapVil) approach was used in this research. Ecological, economic and social dimensions were evaluated. Sustainability index for about 51-75 (suffi-cient) achieved by 43 villages for ecological dimension, 38 villages for economic dimension and 29 villages for social dimension. Attributes used to determine ecovillage’s sustainability in this research were valued well and acceptable, proved by stress value which less than 25%, R-square (R2) more than 80% and  the difference between MDS and montecarlo which less than 2% for each dimensions. This research concluded that social dimension has the highest index which 74.66, followed by economic dimension 58.43 and the lowest one is ecological index which 57.68, with all dimensions still categorized as sufficient.